2012
DOI: 10.1099/ijs.0.025916-0
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio jasicida sp. nov., a member of the Harveyi clade, isolated from marine animals (packhorse lobster, abalone and Atlantic salmon)

Abstract: Vibrio jasicida sp. nov., a member of the Harveyi clade, isolated from marine animals (packhorse lobster, abalone and Atlantic salmon) Six isolates of a facultatively anaerobic bacterium were recovered in culture from marine invertebrates and vertebrates, including packhorse lobster (Jasus verreauxi), abalone (Haliotis sp.) and Atlantic salmon (Salmo salar), between 1994 and 2002. The bacteria were Gramnegative, rod-shaped and motile by means of more than one polar flagellum, oxidase-positive, catalase-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Vibrionaceae are ubiquitous marine heterotrophic bacteria whose taxonomy has been extensively studied and revised, especially in the last years (29,43,44,45,46,47). In particular, the new microbiological and molecular trends have recently seen the mutual analysis of phenotypic, genotypic, and environmental variables, as these features are clearly interconnected in bacterial evolution (24,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Vibrionaceae are ubiquitous marine heterotrophic bacteria whose taxonomy has been extensively studied and revised, especially in the last years (29,43,44,45,46,47). In particular, the new microbiological and molecular trends have recently seen the mutual analysis of phenotypic, genotypic, and environmental variables, as these features are clearly interconnected in bacterial evolution (24,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Balcazar et al (2012) proposed classification of the strain CECT 7692 T as the type strain of V. inhibens in 2012, but the species name was formally included in a Validation List in 2015 (Orren & Garrity, 2015). The name V. jasicida was validly described in 2012 (Yoshizawa et al, 2012) and has a priority over V. The parsimonious analysis found a single most-parsimonious tree (tree length=61 726). Numbers at the nodes are jackknife resampling values, some were omitted for clarity.…”
mentioning
confidence: 99%
“…Overall phenotypic character was found to be very similar between CECT 7692 T and two representative V. jasicida strains. Furthermore, previous studies have shown that V. inhibens CECT 7692 T has a cellular fatty acids composition very similar to that of V. jasicida (Balcazar et al, 2012;Yoshizawa et al, 2012).…”
mentioning
confidence: 99%
“…However, external colonization was generally lacking, suggesting that the cuticle is not a preferred microenvironment for V. owensii DY05 and that unaided invasion through the cuticle is a less likely portal of entry. Diggles et al (12) demonstrated that experimentally injured S. verreauxi phyllosomas were more susceptible to V. jasicida (formerly V. harveyi [53]) in similar immersion experiments and suggested that inadvertent injuries acquired during experimental processing could have contributed to some inconsistent mortality patterns (12).…”
Section: Discussionmentioning
confidence: 99%